RADIATION SYNTHESIS OF POLY(VINYL ALCOHOL) PVA–(POLYVINYL PYRROLIDONE) PVP FOR IMMOBILIZATION OF CAPTOPRIL - Hariyanti Hariyanti; Erizal Erizal; M Yasin Yunus; Indah Lestari; Ditri Risska Rahmadhani (Jurnal Sains Materi Indonesia, 2020)
RADIATION SYNTHESIS OF PVA POLY(VINYL ALCOHOL)–PVP (POLYVINYLPYRROLIDONE) for IMMOBILIZATION OF CAPTOPRIL. The aim of this work is to prepare Polyvinyl alcohol (PVA)- Polyvinylpyrrolidone (PVP) hydrogel with varying irradiation doses and drug dose to be used as a matrix for immobilization and control drug release of captopril. Immobilization and release of captopril in PVA-PVP hydrogel copolymer have been carried out. A mixture of PVA-PVP (6:4 w/w) solution containing captopril (10-20 mg), freeze-thawing, irradiated using gamma rays at various irradiation doses (0-20 kGy). The gel fraction and water absorption were determined gravimetrically. The pores structure of hydrogels were observed using SEM (Scanning Electron Microscope). The captopril released from hydrogel in NaCl 0.9% solution was measured using a UV-Vis spectrophotometer. After evaluated, it was found that with increasing dose up to 20 kGy, the gel fraction increases, and water absorption decreases, and the cumulative drug released decreases. SEM measurement showed that hydrogel had heterogeneous pores. PVA-PVP hydrogel prepared using gamma rays can be considered as a matrix for drug release.